DIVERSIFIKASI OLAHAN IKAN LOKAL CAKALANG SEBAGAI UPAYA PENINGKATAN SKILL PADA IBU BALITA STUNTING DI PESISIR CILALLANG MAJENE - Rahmaniah; Masniati; Risnani; Mutia Salsabila (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Banggae Subdistrict is one of the highest producers of capture fisheries in Majene Regency, with a production of 2,598 tons in 2024, making the fisheries sector one of the most promising sectors for development. However, the community of Cilallang in Banggae Subdistrict has not optimized fish processing. Despite the high fish production, diversifying local fish processing could also be an alternative to improve the nutritional status of toddlers. Data on the nutritional status of toddlers, particularly stunting in Banggae Subdistrict, shows a rate of 30.82%. This means that stunting is still a nutritional problem for the community. Therefore, as part of the optimization of food processing based on local food, community service was carried out focusing on the diversification of local skipjack tuna food through the production of fish-based meatballs and nuggets. The results of the community service program showed that after the education, there was an increase in mothers' knowledge about the importance of fish consumption and the importance of diversifying fish processing. There was also an increase in the skills of mothers of toddlers after the demonstration of making fish-based nuggets and meatballs. The community service program targeted a group of 12 housewives with stunted toddlers. The issue addressed was encouraging innovation and creativity among the group of mothers, particularly in terms of diversifying the processing of local skipjack tuna as an effort to improve the skills of mothers of stunted toddlers in the Cilallang Majene coastal area. Through more varied fish products, it is hoped that toddlers will enjoy eating fish to support improved nutritional status and reduce stunting rates in the Cilallang area. The results of the community service program show that after the education, there was an increase in mothers' knowledge about the importance of fish consumption and the importance of diversifying fish products, as well as an increase in the skills of mothers of toddlers after demonstrations on making fish-based nuggets and meatballs.